2001
DOI: 10.1109/55.962647
|View full text |Cite
|
Sign up to set email alerts
|

Thin tunnel oxide grown on silicon substrate pretreated by CF4 plasma

Abstract: High tunneling current and large resistance against stress were the main issue of tunnel oxide for scaling down the operation voltage of EEPROMs. In this letter, thin-tunnel oxides grown on a CF 4 pretreated silicon substrate were prepared and investigated for the first time. The fabricated oxide has about three orders of tunneling current higher than that of control one; furthermore, the stress induced anomalous and low electric field leakage currents were greatly suppressed. The improvement could be contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…10,12 Recently, the authors reported a simple fabrication process to grow fluorinated oxides with a high tunneling current and low leakage current. 13 This study investigates the electrical and physical characteristics of MOSFETs with this fluorinated oxide, pretreated with CF 4 plasma.…”
mentioning
confidence: 99%
“…10,12 Recently, the authors reported a simple fabrication process to grow fluorinated oxides with a high tunneling current and low leakage current. 13 This study investigates the electrical and physical characteristics of MOSFETs with this fluorinated oxide, pretreated with CF 4 plasma.…”
mentioning
confidence: 99%